Waste Management and Its Contribution to the Sustainable Development Goals at Dhurakij Pundit University, Thailand - Aumnad Phdungsilp (Journal of Sustainability Perspectives, 2022)
The Sustainable Development Goals (SDGs) provide the guidance for the society moving to the sustainability pathways. University is a second home for staffs, students and future leaders and play a key role in achieving the SDGs. This study aims to assess the contribution of waste management in the achievement of the SDGs and their relevant targets. The assessment was performed using the contribution scoring matric that consists of five points and five scoring magnitudes. Using a case study of Dhurakij Pundit University (DPU) in Thailand, the results found that waste management is directly contributed to the SDG 11 (Sustainable cities and communities), SDG 12 (Responsible consumption and production) and SDG 14 (Life below water). The analysis revealed that waste management has direct positive contributions on reducing the environment impact of cities (Target 11.6), enhancing resource use efficiency (Target 12.2), reducing food waste and losses (Target 12.3), reducing waste generation and promoting recycling and reuse (Target 12.5), and preventing and reducing marine pollution from land-based activities (Target 14.1). Waste management is not only having the positive impact of the SDGs but it also contributes to a healthy university during the COVID-19 pandemic and afterward.Keyword: Living Lab, Waste management, Sustainable Development Goals, UI GreenMetric